Pengaruh Layanan Agen Pegadaian dan Digital Service terhadap Kinerja PT Pegadaian Cabang Kupang - Rambu Jenika Puteri Cendana; Reyner F. Makatita; Maria Indriyani Hewe Tiwu (Universitas Veteran Bangun Nusantara, 2024)
This research aims to determine the influence of pawnshop agent services and digital services on the performance of PT Pegadaian Kupang Branch. The type of research used is quantitative research using primary data. The sampling technique used in this research was saturated sampling. So in this study the sample used was the entire population, namely pawnshop agents. The data analysis techniques used in this research include instrument testing, multiple linear regression model estimation, classical assumption testing and hypothesis testing using eviews12 software. The results of this research show that the pawnshop agent variable has an influence on the performance of PT Pegadaian Kupang Branch, the digital service variable has an influence on the performance of PT Pegadaian Kupang Branch. So simultaneously the pawnshop agent and digital services variables influence the performance of PT Pegadaian Kupang Branch.